Measuring Aggregate Welfare in Developing Countries : How Well Do National Accounts and Surveys Agree? - Ravallion, Martin (World Bank, Washington, DC, 2014)
In a data set for developing, and transition economies, the author finds that private consumption per capita, based on national accounts, deviates on average from mean household income, or expenditure based on national sample surveys. Growth rates also differ systematically, so that the ratio of the survey mean to the national accounts mean, tends to fall over time. But there are revealing exceptions to these general findings. The aggregate difference in the levels is due more to income surveys, than to expenditure surveys. And there are strong regional effects; for example, the severe data problems in the transition economies of Eastern Europe, and Central Asia, means that there is negligible correlation in that region, between growth rates from national accounts, and those from household surveys.